Close Readers : Humanism and Sodomy in Early Modern England - Stewart, Alan, 1967- (Book collections on Project MUSE., 1997)
Humanism, in both its rhetoric and practice, attempted to transform the relationships between men that constituted the fabric of early modern society. So argues Alan Stewart in this ground-breaking investigation into the impact of humanism in sixteenth-century England. Here the author shows that by valorizing textual skills over martial prowess, humanism provided a new means of upward mobility for the lowborn but humanistically trained scholar: he could move into a highly intimate place in a nobleman's household that was previously not open to him. Because of its novelty and secrecy, the intimacy between master and scholar was vulnerable to accusations of another type of intimacy--sodomy. In comparing the ways both humanism and sodomy signaled a new economy of social relations capable of producing widespread anxiety, Stewart contributes to the foray of modern gay scholarship into Renais-sance art and literature. The author explores the intriguing relationship between humanism and sodomy in a series of case studies: the Medici court of the 1470s, the allegations against monks in the campaign to suppress the English monasteries, the institutionalized beating of young boys, the treacherous circle of the doomed Sir Thomas Seymour, and the closet secretaries of Elizabeth's final years. Stewart's documentation comes from a wide range of underused materials, from schoolboys' grammar books to political writings, enabling him to reconstruct frequently misunderstood events in their original contexts. Originally published in 1997. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.